2009
DOI: 10.1002/ejsp.667
|View full text |Cite
|
Sign up to set email alerts
|

Imitation of emotion: When meaning leads to aversion

Abstract: Can imitation lead to less liking? Previous research on mimicry and imitation suggests that imitation should lead to more liking, at least when it concerns neutral behaviours. In the present studies, we looked at behaviour with a clear message: Facial expressions. As predicted, we found in two studies that an affiliative facial expression (happiness) leads to more liking when imitated, whereas a non-affiliative facial expression (anger) leads to less liking when imitated. Thus, imitating someone does not alway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Both effects were absent for participants scoring low on communal strength (exchange relationships). Furthermore, we found that strangers' angry faces were mimicked, consistent with other research on facial responses (e.g., Van der Velde et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Both effects were absent for participants scoring low on communal strength (exchange relationships). Furthermore, we found that strangers' angry faces were mimicked, consistent with other research on facial responses (e.g., Van der Velde et al, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…First, we investigated the possibility that accommodation may also take place spontaneously. We hypothesized that one's partner's angry face would be accommodated by a spontaneous smile, whereas a stranger's angry face would be met with mimicry (see also Epstude & Mussweiler, 2009;Van der Velde, Stapel, & Gordijn, 2010). Second, we investigated the relation between more abstracted and less abstracted, more experiential representations of relationships.…”
Section: Studymentioning
confidence: 99%
“…Congruent expressions (e.g. frowning) to displays of anger are thus unlikely to increase affiliation and might in fact convey hostile intention and initiate agonistic interactions (van der Velde et al, 2010;Van Kleef, 2010). The case of fear deserves some more elaboration.…”
Section: Does Oxytocin Promote Mimicry?mentioning
confidence: 98%
“…The effect of mimicry on attitudes is that of increased favoring of the mimickee (e.g., larger tips offered to bartenders mimicking speech and facial expression; Van Baaren et al, 2003 ). The mechanism is reciprocal – the mimicker is more positively inclined towards the person he mimics ( Chartrand and Bargh, 1999 ; van Baaren et al, 2004 ; van der Velde et al, 2010 ). Some researchers have reported that mimicking stimulates interpersonal closeness as well as perceived similarity to the self, and enhances the flow of interaction ( Bernieri and Rosenthal, 1991 ; Chartrand and Bargh, 1999 ; Bailenson and Yee, 2005 ; Stel et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%